High frequency, sustained T cell responses to PARV4 suggest viral persistence in vivo - Simmons, R; Sharp, C; Sims, S; Kloverpris, H; Goulder, P; Simmonds, P; Bowness, P; Klenerman, P (Oxford University Press, 2011)
Background. Parvovirus 4 (PARV4) is a recently identified human virus that has been found in livers of patients infected with hepatitis C virus (HCV) and in bone marrow of individuals infected with human immunodeficiency virus (HIV). T cells are important in controlling viruses but may also contribute to disease pathogenesis. The interaction of PARV4 with the cellular immune system has not been described. Consequently, we investigated whether T cell responses to PARV4 could be detected in individuals exposed to blood-borne viruses. Methods. Interferon γ (INF-γ) enzyme-linked immunospot assay, intracellular cytokine staining, and a tetrameric HLA-A*0201-peptide complex were used to define the lymphocyte populations responding to PARV4 NS peptides in 88 HCV-positive and 13 HIV-positive individuals. Antibody responses were tested using a recently developed PARV4 enzyme-linked immunosorbent assay. Results. High-frequency T cell responses against multiple PARV4 NS peptides and antibodies were observed in 26% of individuals. Typical responses to the NS pools were > 1000 spot-forming units per million peripheral blood mononuclear cells. Conclusions. PARV4 infection is common in individuals exposed to blood-borne viruses and elicits strong T cell responses, a feature typically associated with persistent, contained infections such as cytomegalovirus. Persistence of PARV4 viral antigen in tissue from HVC-positive and HIV-positive individuals and/or the associated antiviral T cell response may contribute to disease pathogenesis.